Hidden umbilical anomalies: case reports of newborns with a persistent urachus and a persistent vitellointestinal duct - Aleksandra Kątnik; Klaudia Szala; Grzegorz Kudela; Agnieszka Wiernik (Annales Academiae Medicae Silesiensis)
Introduction: Anomalies in the umbilical region of newborns encompass a range of congenital malformations that require careful diagnosis. These conditions may lead to delayed healing of the umbilical stump, discharge from the navel, and pose challenges for pediatricians. Among these, vitellointestinal duct (VID) anomalies are the most common, occurring in approximately 2–3% of the population. The VID, an embryonic structure connecting the yolk sac to the primitive midgut, normally regresses during development. Failure of this process can result in various anomalies, the most common being Meckel’s diverticulum. Similarly, urachal anomalies arise when embryonic urachus persists, potentially presenting as abnormalities at the umbilicus. Case reports: A 6-day-old male newborn with a draining fistula at the umbilicus was transferred to our institution with a suspected diagnosis of persistent urachus. After admission, the visible fistula was catheterized under ultrasound guidance, revealing a connection to the intestinal loops. This finding indicated a diagnosis of a persistent VID, which was subsequently excised. Another patient was a 15-day-old female newborn with a bladder defect detected during a prenatal ultrasound examination. An everted patent urachus was diagnosed after birth, which was subsequently treated by means of surgical excision. Conclusions: Abnormalities in the umbilicus may raise the suspicion of persistent fetal structures. A thorough physical examination, supplemented by ultrasound and catheterization, can effectively make the correct diagnosis. Surgical treatment is recommended, involving resection of the persistent urachus or resection of the persistent VID with the bowel fragment.